Microfiltration of deformable microgels. Issue 31 (22nd July 2016) - Nir, Oded; Trieu, Tony; Bannwarth, Sebastian; Wessling, Matthias
Abstract : Deposition patterns of sub-micron size microgels inside a porous membrane are identified by analyzing electrical impedance and hydraulic resistance data, recorded simultaneously during microfiltration of microgel suspensions. Understanding the separation, concentration and purification processes of soft nanoparticles is essential for numerous applications in water filtration, bioprocessing and blood separation. Abstract : Understanding the separation, concentration and purification processes of soft nanoparticles is essential for numerous applications in water filtration, bioprocessing and blood separation. Here we report unique translocation and rejection features of sub-micron sized microgels during frontal filtration using membranes having micron-sized porosity. Simultaneously measuring the increase in hydraulic resistance and electrical impedance change allows us to clearly distinguish two deposition phases: (a) microgel accumulation within the depth of the membrane porosity and (b) subsequent formation of a thin gel layer on the membrane surface. Such distinction is impossible using only classical hydraulic resistance analysis. The methodology only requires the ratio of microgel to solution conductivity as an input parameter.